If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4a + -9)(4a + -9) = 0 Reorder the terms: (-9 + 4a)(4a + -9) = 0 Reorder the terms: (-9 + 4a)(-9 + 4a) = 0 Multiply (-9 + 4a) * (-9 + 4a) (-9(-9 + 4a) + 4a * (-9 + 4a)) = 0 ((-9 * -9 + 4a * -9) + 4a * (-9 + 4a)) = 0 ((81 + -36a) + 4a * (-9 + 4a)) = 0 (81 + -36a + (-9 * 4a + 4a * 4a)) = 0 (81 + -36a + (-36a + 16a2)) = 0 Combine like terms: -36a + -36a = -72a (81 + -72a + 16a2) = 0 Solving 81 + -72a + 16a2 = 0 Solving for variable 'a'. Factor a trinomial. (9 + -4a)(9 + -4a) = 0Subproblem 1
Set the factor '(9 + -4a)' equal to zero and attempt to solve: Simplifying 9 + -4a = 0 Solving 9 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4a = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4a = 0 + -9 -4a = 0 + -9 Combine like terms: 0 + -9 = -9 -4a = -9 Divide each side by '-4'. a = 2.25 Simplifying a = 2.25Subproblem 2
Set the factor '(9 + -4a)' equal to zero and attempt to solve: Simplifying 9 + -4a = 0 Solving 9 + -4a = 0 Move all terms containing a to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4a = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4a = 0 + -9 -4a = 0 + -9 Combine like terms: 0 + -9 = -9 -4a = -9 Divide each side by '-4'. a = 2.25 Simplifying a = 2.25Solution
a = {2.25, 2.25}
| 4x^2-66+140=0 | | 4x+25-2x+25=6 | | 6(1+2x)=5(3x-1)-4 | | (a-10)(a+10)= | | a-3=5a-65 | | (y^2+2)(5y+8)= | | D-5=-16 | | (x+6)(x+4)= | | 3(2x-6)=2(2x+1) | | (7x-1)-(4x+5)= | | 4(2x-3)=2(3x-5) | | y=9x-3 | | 2(x+5)=3x | | 17x^2-7x^2-13= | | 2(2x+5)=5x+5 | | 68=14m+40 | | 6a+36=4 | | -7z^0= | | 12x+4y=-144 | | 9z=-72 | | 3(2x+1)=2x+11 | | 3x+7=32-2x | | (a^12b^2)(a^5b)= | | 5x+12=7+15x-5x | | 9a+36=4 | | 5x-2=40-x | | t^2-20t+44= | | 3x+1=5x-13 | | t^2-4t+12=0 | | 17=y-57 | | 8z+6=7z | | 2t^2-20t+44=0 |